Aerobic physical exercise and prolactin levels in blood during breastfeeding in woman with Hashimoto’s thyroiditis – A case report - Bubnjević, Ksenija; Ugarković, Dušan; Kovačević, Jelena (Vojnosanitetski pregled, 2021)
Introduction. The World Health Organization (WHO) exclusively recommends breastfeeding for the first six months of the newborn life. Many factors affect milk production. Physical exercise can significantly affect prolactin secretion in the blood. Case report. A respondent in this study was a primipara (33 years old) diagnosed with Hashimoto’s thyroiditis and a singleton pregnancy. During pregnancy and after the childbirth, she continued with light to moderate physical exercise. During the first six months after the childbirth, the light to moderate intensity aerobic exercise had no negative impact on the blood level of prolactin and growth and development of the child. Conclusion. In this case study, light to moderate intensity aerobic exercise had no negative impact on the level of prolactin in the blood during the first six months after the childbirth in a woman with Hashimoto’s thyroiditis.